2016
DOI: 10.1093/ntr/ntw161
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Smoking in the Roma Population Seems to Have No Genetic Background

Abstract: This is the first study designed to determine whether genetic background exists behind the harmful behavior of the smoking of the Roma population. Although the frequencies of susceptible and protective alleles strongly differ between the Hungarian Roma and general populations, it is shown that calculated GRSs being significantly higher in the general population, which do not support the hypothesis on the genetic susceptibility of the Roma population. Interventions aimed at smoking cessation in the Roma populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…effects beyond increased susceptibilities to some rare health conditions (e.g. Diószegi et al 2017;Fiatal et al 2016;Iovita et al 2004;Kalaydjieva et al 2001;Martinez-Cruz et al 2016;Pikó et al 2017;Szalai et al 2014). This is in line with findings on other ethnic disparities in indicating complex reproductive segregation patterns faced by minority ethnic groups (Bhopal 2015;Dressler et al 2005;Smith 2000).…”
Section: Figure 12 Health Indicators For Roma and The General Populasupporting
confidence: 64%
See 1 more Smart Citation
“…effects beyond increased susceptibilities to some rare health conditions (e.g. Diószegi et al 2017;Fiatal et al 2016;Iovita et al 2004;Kalaydjieva et al 2001;Martinez-Cruz et al 2016;Pikó et al 2017;Szalai et al 2014). This is in line with findings on other ethnic disparities in indicating complex reproductive segregation patterns faced by minority ethnic groups (Bhopal 2015;Dressler et al 2005;Smith 2000).…”
Section: Figure 12 Health Indicators For Roma and The General Populasupporting
confidence: 64%
“…Accordingly, and alike for other ethnic health-disparities (Diez Roux 2012; Dressler et al 2005), the insignificance of genetic influences behind poor Roma health status has been confirmed empirically. The only genetic susceptibilities identified in Roma are higher frequencies of a handful of gene-alleles causing rare diseases, peaking in some localities due to total social (reproductive) segregation from neighbouring Chapter 7 populations (Diószegi et al 2017;Fiatal et al 2016;Kalaydjieva et al 2001;Martinez-Cruz et al 2016). Let's emphasize that this is despite a previous disproportionate focus of research specifically on possible genetic influences (Hajioff and McKee 2000;Zeman et al 2003).…”
Section: Why Should Genes Come Last?mentioning
confidence: 99%
“…However, when considering smoking in Roma ethnics, it was shown that the lower socioeconomic status cannot fully mediate the disparities with non-Roma inhabitants [31]. This left room for the search for a genetic predisposition, which was recently shown not to play a significant role in this risk behavior in Roma ethnics, thus suggesting that focus should be placed on cultural and environmental factors [32].…”
Section: Cardiovascular Profilementioning
confidence: 99%
“…Accordingly, and alike for other ethnic health disparities (Diez Roux 2012; Dressler et al 2005), the insignificance of genetic influences behind poor Roma health status has been confirmed empirically. The only genetic susceptibilities identified in Roma are higher frequencies of a handful of gene alleles causing rare diseases, peaking in some localities due to total social (reproductive) segregation from neighbouring populations (Diószegi et al 2017; Fiatal et al 2016; Kalaydjieva et al 2001; Martinez-Cruz et al 2016). Let us emphasize that this is despite a previous disproportionate focus of research specifically on possible genetic influences (Hajioff and McKee 2000; Zeman et al 2003).…”
Section: Why Should Genes Come Last?mentioning
confidence: 99%